Trans-ungual delivery of itraconazole hydrochloride by iontophoresis. (July 2015) - Kushwaha, Avadhesh; Jacob, Melissa; Shiva Kumar, H. N.; Hiremath, Shobharani; Aradhya, Sacchidanand; Repka, Michael A.; Murthy, S. Narasimha
Abstract Itraconazole (ITR) is a potent antifungal drug. However, poor aqueous solubility limits its permeation ability across the human nail plate. Therefore, in this project, ITR was converted to hydrochloride salt (ITR-HCl) to improve its solubility and to render it amenable to iontophoresis. ITR-HCl was characterized by spectroscopic methods and antifungal efficacy was evaluated in comparison to the base. In vitro and ex vivo transport studies (passive and iontophoresis) were carried out across the porcine hoof membrane and excised human cadaver toe using two different protocols; continuous delivery of drug for 24 h and pulsed delivery of drug for 3 days (8 h/day). The antifungal efficacy of ITR-HCL was comparable to ITR. Iontophoresis was found to be more effective than passive mode of delivery of ITR-HCL. In both iontophoresis as well as passive mode of delivery, the pulsed protocol resulted in more ungual and trans-ungual delivery of drug than continuous protocol. ITR-HCL could be delivered into and across the nail plate by iontophoresis. Human cadaver toe appears to be a good model to investigate the ungual delivery of drugs.